2007
DOI: 10.1063/1.2755665
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic couplings from time-dependent density functional theory: Formulation in the Casida formalism and practical scheme within modified linear response

Abstract: We present an efficient method to compute nonadiabatic couplings (NACs) between the electronically ground and excited states of molecules, within the framework of time-dependent density functional theory (TDDFT) in frequency domain. Based on the comparison of dynamic polarizability formulated both in the many-body wave function form and the Casida formalism, a rigorous expression is established for NACs, which is similar to the calculation of oscillator strength in the Casida formalism. The adiabatic local den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 49 publications
1
76
0
Order By: Relevance
“…Hu and co-workers have further developed the Chernyak-Mukamel approach for computation of first-order nonadiabatic coupling vectors between the ground state and the first excited state [74][75][76]. Send and Furche have shown that the previous result neglects molecular orbitals derivatives [77].…”
Section: Surface Hopping Dynamics With Dft Excited Statesmentioning
confidence: 96%
“…Hu and co-workers have further developed the Chernyak-Mukamel approach for computation of first-order nonadiabatic coupling vectors between the ground state and the first excited state [74][75][76]. Send and Furche have shown that the previous result neglects molecular orbitals derivatives [77].…”
Section: Surface Hopping Dynamics With Dft Excited Statesmentioning
confidence: 96%
“…As in the NVPT approach based on the completeadiabatic form of the electron-nuclear wave function [19], the first-order perturbation to the electronic wave function represents the effect of the non-adiabatic coupling between the ground and the excited electronic states. Within a fully non-adiabatic approach [59][60][61][62][63][64][65][66][67][68], it would be possible to compute Eq. (32).…”
Section: Nuclear Velocity Perturbation Theorymentioning
confidence: 99%
“…Nonadiabatic coupling vectors between the ground and any excited states can in principle be computed exactly from LR-TDDFT, [44][45][46][47][48] while couplings between excited states are only approximated in the linear-response formalism. 49 Nevertheless, it has been shown that the adiabatic approximation to LR-TDDFT (which is effectively the only practical option) cannot properly describe couplings between the first excited state and the ground state.…”
Section: Iia Brief Summary Of Full and Ab Initio Multiple Spawningmentioning
confidence: 99%